PENGARUH STRATEGI ORIENTASI ORGANISASI TERHADAP MANAJEMEN RANTAI PASOK HIJAU DAN KINERJA BISNIS - Henilia Yulita (IKOPIN, 2019)
Environmental pollution is a major problem that has the potential to cause the extinction of mankind on earth if it is not immediately addressed. Companies that have adopted green supply chain management believe that environmental awareness is a